Type I Interferon in Human Autoimmunity - Timothy B. Niewold (Frontiers Research Topics, 2015)
The type I interferon system plays a critical role in host defense in health, and a growing body of literature suggests that type I interferon is a critical mediator of human autoimmune disease. Type I interferons function as a bridge between the innate and adaptive immune systems, and as such play an important role in setting thresholds for response against self antigens. Many investigators have focused on the role type I interferons play in autoimmune disease. This fascinating and rapidly growing body of literature encompasses many different autoimmune diseases, including systemic lupus erythematosus, type I diabetes, multiple sclerosis, and others. In this Research Topic, we provide a comprehensive overview of the various roles type I interferons play in autoimmune diseases, with a focus on human immunology.